Farewell Missives - Braude, Stephen (Journal of Scientific Exploration, 2022)
This is a particularly rich issue of the JSE. And a hefty one. Its size is due primarily to two quite lengthy essays, one by Bryan Williams and one by Michael Sudduth. Of course, all of this issue’s articles and reviews are worth reading; that’s why we’re publishing them. But these two huge essays merit a few extra comments. Bryan Williams has given us something that I and various SSE members have hoped for over the years, a detailed review of a specific line of anomalistic research—the kind of article that would be useful to both veterans and newcomers to edge science. I’ve often tried to recruit such an opus from SSE colleagues at our conferences, hoping my considerable charm would dazzle them into accepting the opportunity. I’ve even been assured on several occasions that the solicited reviews would be forthcoming. But only Bryan, so far, has delivered the goods, a splendid essay surveying research on PK with random number generators. Not surprisingly, this review took Bryan a long time to write, and I want to thank him, not only for the result, but for his tenacity. Michael Sudduth’s essay is a forensic tour de force (as befits an admirer of the TV detective show Columbo)—an unprecedently detailed critique of the James Leininger case of ostensible reincarnation. That case is both complicated and messy, and it illustrates a general problem with CORT investigations that I’ve dubbed the Problem of Investigative Intricacy.